MAKING THE ROTARY TABLE LOCK OF SCHAUBLIN 13 MILLING MACHINE - Adhan Efendi (VANOS Journal of Mechanical Engineering Education, 2019)
The milling machine in the workshop of Bandung Manufacturing Polytechnic works not too optimally in the process of the incision. This is due to the disappearance of two rotary table lock milling machine which makes the cutting process less than perfect. This study attempts to make a rotary table lock milling machines schaublin 13. The stages in this study are the study of literature, making work drawings, preparing tools and materials, and execution. Data obtained in the process of making the rotary table lock was analyzed qualitative descriptive. The results of this study are (1) there are several parameters that must be considered such as spindle rotation, feeding motion, and depth of cut, (2) the milling process must be carried out in accordance with the procedure to ensure the operator and engine safety, (3) the milling process must be carried out carefully so that the workpiece can match to the work drawings. Perseverance in the milling process is needed for maximum results